Exploring the role of mixed reality education in maternal self efficacy and satisfaction with breastfeeding - Andrés Montoya-Moncada; Laura Cuero-Ríos; Fabio Rodríguez-Morales; Mateo Perdigón; Sergio Agudelo-Pérez (Scientific Reports)
Abstract Breastfeeding is widely recognized as the optimal form of infant nutrition; however, exclusive breastfeeding (EBF) rates remain low worldwide. Psychological factors such as maternal self-efficacy and satisfaction play a key role in breastfeeding success. This randomized controlled trial evaluated whether a mixed-reality educational strategy could improve maternal self-efficacy and breastfeeding satisfaction. A total of 58 pregnant women in their third trimester were randomly assigned to receive either mixed reality plus traditional counseling or traditional counseling alone. Breastfeeding self-efficacy and satisfaction were measured one week postpartum using validated instruments. No statistically significant differences were found between the groups in self-efficacy (mean scores 63.3 vs. 63.1) or satisfaction (133.5 vs. 134.0). However, both groups demonstrated remarkably high rates of exclusive breastfeeding during the first week of life (93.1%), far exceeding the national and global average. Although the mixed-reality intervention did not yield superior outcomes within the short follow-up period, the findings highlight the potential benefits of structured prenatal education in enhancing breastfeeding practices. This low-cost immersive approach may be particularly relevant in middle- and low-income settings. Further research with a larger sample size and extended follow-up is required to assess the long-term impact and broader applicability of mixed reality in maternal health education. Clinical trial registration: https://ClinicalTrials.gov (NCT06800521; registered on 30/01/2025).